2023
DOI: 10.3390/microorganisms11020345
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and Physiological Characterization of Morchella Mitospores and Their Relevance in the Understanding of the Morel Life Cycle

Abstract: Morels, which belong to the Ascomycete genus Morchella, are highly valued edible fungi treasured by gourmet chefs worldwide. Some species are saprotrophic and others are able to form facultative mycorrhizal-like associations with plant roots without establishing true ectomycorrhizal symbioses. In general, it is considered that the formation of asexual spores, or mitospores, is an important step in the life cycle of morels. However, ultrastructure characterization and physiological attributes of morel mitospore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The morel was sown on the 35th day after fumigation, and the dosage of spawn was 300 g/m 2 . Seven days after sowing, morel mitospores, which was previously considered as asexual conidia ( Liu et al, 2023 ), appeared on the soil surface. On the 10th day, exogenous nutrient bags punched on the side that would be in contact with the soil were placed on the soil surface.…”
Section: Methodsmentioning
confidence: 99%
“…The morel was sown on the 35th day after fumigation, and the dosage of spawn was 300 g/m 2 . Seven days after sowing, morel mitospores, which was previously considered as asexual conidia ( Liu et al, 2023 ), appeared on the soil surface. On the 10th day, exogenous nutrient bags punched on the side that would be in contact with the soil were placed on the soil surface.…”
Section: Methodsmentioning
confidence: 99%
“…On day 10, two exogenous nutrition bags (ENBs, containing 330 g substrate [5]) were laid on the soil surface and covered by mulch to maintain the temperature, humidity, and dim sunlight. On day 35, white and powdery conidial mats [12] emerged from the soil surface, and soil samples were collected (referred to as conidial stage samples (CD)). On day 46, the ENBs were removed, and drop watering was applied for at least 12 h to trigger morel fructification.…”
Section: Experimental Settings and Cultivation Protocolmentioning
confidence: 99%
“…The results showed that the cell wall of the mitospores of M. sextelata was very thin, which was the thinnest structure during the life cycle of Morchella. Based on the combination of both: (i) A very low germination rate, usually around 1/100,000; and (ii) the rapid aging of the germinating strains, it was presumed that morel mitospores had lost the rapid propagation and reproduction function like conidia and that they behaved more like microspores (spermatium) that played a mating function in fungi [ 60 , 61 ]. However, as a gamete, the time and space of fertilization (mating) are still unknown.…”
Section: Relevance On Biological Research For Steady Cultivation Indu...mentioning
confidence: 99%